Improvement of skeletal muscle insulin sensitivity by 1 week of SGLT2 inhibitor use. Issue 7 (July 2020) - Goto, Yuka; Otsuka, Yoshie; Ashida, Kenji; Nagayama, Ayako; Hasuzawa, Nao; Iwata, Shimpei; Hara, Kento; Tsuruta, Munehisa; Wada, Nobuhiko; Motomura, Seiichi; Tajiri, Yuji; Nomura, Masatoshi
Abstract : Background and Aims: : It is currently unclear whether sodium–glucose co-transporter 2 (SGLT2) inhibitor administration can improve the insulin sensitivity as well as rapidly reduce plasma glucose concentrations in humans during the early phase of treatment initiation. This study aimed to investigate the effect of SGLT2 inhibitor on insulin sensitivity in the early phase of treatment initiation. Methods and Results : This single-center, open label, and single-arm prospective study recruited 20 patients (14 men) with type 2 diabetes mellitus (T2DM). We examined the patients' metabolic parameters before and 1 week after SGLT2 inhibitor (10 mg/day of empagliflozin) administration. The glucose infusion rate (GIR) was evaluated using the euglycemic hyperinsulinemic glucose clamp technique. Changes in laboratory and anthropometric parameters before and after SGLT2 inhibitor administration were analyzed according to the change in the GIR. The BMI, body fat amount, skeletal muscle amount, systolic blood pressure, and triglyceride level significantly decreased along with the treatment, while urinary glucose level and log GIR value significantly increased. Notably, changes in the GIR after SGLT2 inhibitor administration, which indicated improvement in peripheral insulin sensitivity, were negatively correlated with T2DM duration and positively with reduction in fluctuation of daily plasma glucose profiles before and after treatment. Conclusion : SGLT2 inhibitor improved insulin sensitivity in the skeletal muscle independent of anthropometric changes. Patients with short duration of T2DM and insulin resistance can be good candidates for short-term SGLT2 inhibitor administration to improve insulin sensitivity in the skeletal muscle.